Comparison of pulmonary function of women in 2nd trimester and non-pregnant women, in central Uttar-Pradesh, India - Khan, Humail; Jaiswal, Kirti Jaiswal; Sant, Santosh K.; Kumar, Sandip (International Journal of Research in Medical Sciences, 2019)
Background: Pregnancy is nothing but a process of maternal adaptation to meet the increasing needs of the growing foetus. Significant changes in the highly sensitive respiratory system occurs during pregnancy to fulfil increased demands as well as to combat stress of pregnancy. Although many studies have been done in India to study the Pulmonary Functions during pregnancy, but due to paucity of such study in central Uttar-Pradesh this study was planned. Methods: This study was carried out on 353 2nd trimester pregnant women coming to ANC clinic of Obstetrics and Gynaecology Department of Uttar-Pradesh University of Medical Sciences, Saifai, Etawah, pulmonary function parameters were recorded using Computer based Digital Spirometer. Data were compared with pulmonary function parameters of age matched 353 Non-Pregnant controls. Parameters studied were FVC, FEV1, FEV1/FVC, PEFR and MVV. Results: FVC, FEV1, FEV1/FVC and PEFR was found less in pregnant women as compared to Non-pregnant women, difference was statistically highly significant (P<0.01). MVV was also found less in pregnant women but it was insignificant (P >0.05). Conclusions: All parameters of PFT are deranged in pregnancy. Matching of other attributes of cases and controls like height, pre-pregnancy weight of cases and weight of controls, Haemoglobin, BMI, could possibly further explain the established relationship of pregnancy and PFT parameter derangements. Perhaps, a longitudinal study in expectant mothers by measuring their PFT parameters in non-pregnant states and then serial follow-up PFT measurement during their pregnancy would be a better approach to look for the effects of pregnancy on PFT parameters.